If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24=-3(x-2)=3
We move all terms to the left:
24-(-3(x-2))=0
We calculate terms in parentheses: -(-3(x-2)), so:We get rid of parentheses
-3(x-2)
We multiply parentheses
-3x+6
Back to the equation:
-(-3x+6)
3x-6+24=0
We add all the numbers together, and all the variables
3x+18=0
We move all terms containing x to the left, all other terms to the right
3x=-18
x=-18/3
x=-6
| 7p-(3p+4)=-1)10 | | -2y=-2y+16 | | 5x+14-4x=6x+10-2x | | 3x+11=16- | | X2-8x+3=0 | | d/3-7=4 | | -g+2(3+g)=-4(8+1) | | 16=2w-4 | | 2p-3=5-2p* | | 130-4x=x | | 31=r/4+2 | | 6-(2x+3)=x+12 | | 4g−124,g=5 | | -g+-4=-9 | | 19×x=21 | | 3/2=15/z | | 9h+4=45 | | q/2+20=16 | | -5=q−9q= | | 3(-9+7x)=57 | | 4(x-9)=-36+4x= | | 17=3g−-8 | | -5=q−9 | | 7=n+20 | | m*10=4 | | 5-2h=9 | | 2x+8-2(-6x-1)=4(x-1) | | 20=-12x-8 | | 5x-48=67 | | 3(5x-39)=2(x+26) | | n-5.9n-6.5=-0.5(n-4.6) | | 8x+8=2x+16 |